A Film Semiotics Study of Representation on Duality Female Character - Umaroh, Liya; Adibatul Maulida (Faculty of Language and Literature, University of Surakarta, 2025)
The abstract Semiotics delves on sign, picture, text, and film scene. The final purpose of this research portrays the duality female representation through film. Descriptive qualitative is used as a research method and observation as the instrument for selecting scenes film as data analysis. Furthermore, the steps on representation go with Roland Barthes’ semiotics and the result of this research can be stated (1) denotation, she is being a superpower woman but vulnerable hearth (2) connotation, complexity of resilient woman attempt to gain patriarchal (3) myth, society prefer to be more critical by woman who bravely challenge the system than man, illustrating a gender imbalance social acceptance. Duality female representation on this film describes either as the visioner or manipulator and how complicated life of modern woman, she has to balance either strength and weakness, woman is able to create new reality but in other hand she has a risk for losing themselves.